Comparison of state and trait confidence on wheelchair tennis and wheelchair badminton athletes / Nagoor Meera Abdullah ... [et al.] - Abdullah, Nagoor Meera; Nordin, Fatin Nabilah; Mohamed Shapie, Mohammad Nizam; Abdul Rahim, Mohd Rahizam; Parnabas, Vincent; Tumijan, Wahidah (Universiti Teknologi MARA, 2021)
An individual's mental state has been identified to play a significant role when performing a sport specific task. This ability leads to the success or failure of every athlete. The purpose of the study is to compare the level of state and trait self-confidence among athletes with disabilities. Total of 100 athletes (n = 100) comprises of 61 wheelchair tennis (WT) athletes and 39 wheelchair badminton (WB) athletes age range between 18-54 years voluntarily participated in the study. The athletes were practicing their sports at least from 2 to 18 years. The study uses the reliable instruments that is State Sport Confidence Inventory (SSCI) and Trait Sport Confidence Inventory (TSCI). The questionnaires were distributed during Malaysia Open Wheelchair Tennis Championship and MBPJ-MPM Paralympics Sport Carnival. Trait Sport Confidence Inventory (TSCI) was distributed among subjects approximately 24 hours before the competition and State Sport Confidence Inventory (SSCI) was distributed among subjects within 1 hour after end of the game. Paired-Sample T-test and Independent-Samples T-test data was analysed and shows mean difference of TSCI and SSCI among WT athletes and WB athletes was significant (P < 0.05). The mean of TSCI in WT is 4.59 and 4.69 in WB. Meanwhile, mean in SSCI for WT is 7.20 and 7.12 in WB. In conclusion, there is no difference in the level of self confidence among wheelchair tennis athletes and wheelchair badminton athletes. Self-confidence has been linked as contributing factors to athletic performance. The current finding can assist coaches and athletes in understanding level of selfconfidence before the competition.